Questionnaire translation, validation and relationship determinants of marital quality with clinical attributes of functional dyspepsia, irritable bowel syndrome and its overlap syndrome in Malay women - Hamid, Nurhazwani (2024)
Functional Dyspepsia (FD), Irritable Bowel Syndrome (IBS), and FD-IBS overlap are common and bothersome disorders affecting people of diverse backgrounds, predominantly women. Research is limited in measurement tools available for marital quality, and the association of marital quality with psychological distress, symptom severity, and quality of life (QoL) of Malay women with FD, IBS, and FD-IBS overlap. Phase I, to develop valid measurement tools for marital quality in the Malay language. Secondly (Phase II), to compare mean differences, correlation between study variables, and to examine path relationships between marital quality with clinical attributes including psychological distress, symptom severity, and QoL among Malay women with FD, IBS, and FD-IBS overlap. Phases I and II were conducted using cross-sectional design and by convenience sampling. Phase I consisted of translation into the Malay language and validation of questionnaires including Revised Dyadic Adjustment Scale (RDAS), Relationship Dynamic Scale (RDS), Short Version Psychological Maltreatment of Women Inventory (PMWI-F), Multidimensional Pain Inventory (MPI), and Coping Strategies Questionnaire-Catastrophizing Scale (CSQ-CAT). All questionnaires were examined for content validity index (CVI), face validity index (FVI), exploratory factor analysis (EFA), and reliability (Cronbach’s alpha). For phase II, first, multivariate analysis of variance (MANOVA) would be used to determine mean differences between variables, second, correlation analysis of all variables and third, path analysis (PA) model to map inter-relationships between variables. All the newly translated Malay questionnaires were found to have CVIs and FVIs > 0.80. There were 150 participants (mean age 34.1 years old, standard deviation (SD)=9.5 years) and 513 participants (mean age 37.2 years old, SD=9.3 years) who have participated in phase I and II respectively. For phase I, all factor loadings were found satisfactory with EFA and the Cronbach’s alpha of RDAS-M, RDSM, PMWI-F-M, MPI-M, and CSQ-CAT-M was ranged between 0.7 and 0.9. For phase II, with MANOVA, the most significant mean differences were seen between groups of FD versus IBS, and FD versus FD-IBS overlap, and the marital quality most significantly affected included consensus, conflict management, negative responses, and solicitous responses. With Pearson correlation analysis, FD demonstrated the most significant correlations with all clinical attributes (r > 0.5). With PA of overall model, the fit indices for FD, IBS, and FD-IBS overlap were found to be acceptable. FD-IBS overlap had the most number of paths (n=30), followed by FD (n=26), and IBS the least (n=24). With PA, the most supported hypothesis for the domains marital quality and symptom severity was demonstrated with FD-IBS overlap. Whereas, for the domain psychological distress, the most supported hypothesis using PA was demonstrated for FD. First, the tools to measure marital quality have been translated into the Malay language, and are validated. Second, there is significant inter-relationships of marital quality with clinical attributes of FD, IBS, and FD-IBS overlap in the Malay women.